Bi Nanoparticles Anchored in N-Doped Porous Carbon as Anode of High Energy Density Lithium Ion Battery - Zhong, Yaotang; Li, Bin; Li, Shumin; Xu, Shuyuan; Pan, Zhenghui; Huang, Qiming; Xing, Lidan; Wang, Chunsheng; Li, Weishan (Nano-Micro Letters, 2018)
A novel bismuth–carbon composite, in which bismuth nanoparticles were anchored in a nitrogen-doped carbon matrix (Bi@NC), is proposed as anode for high volumetric energy density lithium ion batteries (LIBs). Bi@NC composite was synthesized via carbonization of Zn-containing zeolitic imidazolate (ZIF-8) and replacement of Zn with Bi, resulting in the N-doped carbon that was hierarchically porous and anchored with Bi nanoparticles. The matrix provides a highly electronic conductive network that facilitates the lithiation/delithiation of Bi. Additionally, it restrains aggregation of Bi nanoparticles and serves as a buffer layer to alleviate the mechanical strain of Bi nanoparticles upon Li insertion/extraction. With these contributions, Bi@NC exhibits excellent cycling stability and rate capacity compared to bare Bi nanoparticles or their simple composites with carbon. This study provides a new approach for fabricating high volumetric energy density LIBs. Highlights: 1 The Bi nanoparticles anchored in N-doped porous carbon (Bi@NC) composite was prepared by a facile replacement reaction method, in which ultrasmall Bi nanoparticles were homogeneously encapsulated in the carbon matrix 2 The N-doped carbon matrix enhanced the electric conductivity and alleviated the mechanical strain of Bi nanoparticles on Li insertion/extraction due to the larger void space, and Bi@NC exhibits excellent cyclic stability and rate capability for LIBs 3 The strategy developed in this work solves the cyclic instability issue of bismuth as anode for LIBs and provides a new approach to improve high volumetric energy density for electrochemical energy storage devices.